The WS2/AlN heterostructure band alignment by semi-local functional and its optical properties by the Bethe-Salpeter approximation on top of GW calculations. (September 2022) - Yeganeh, Mahboubeh; Boochani, Arash; Yari, Arash; Amiri, Maliheh; Shahraki, Amir Toofani
Abstract: In this study, the electronic properties and band alignment of the heterostructures of WS2 /AlN at three different separation distances of d 1 = 2.77, d 2 = 4.34, and d 3 = 6.37 Å, were investigated by GGA approximation. The calculation of energy changes in terms of volume alternations revealed that the heterostructure at d 2 = 4.34 Å is the most energetically favored configuration. The WS2 /AlN showed the band gap of 1.68, 1.52, and 1.69 eV by GGA at separation distances of d 1, d 2, and d 3, respectively showing the band alignment of type II. Since the accuracy of the optical properties and detecting the excitonic states relies on the accuracy of the band structure, the quasi-particle calculation based on the G0 W0 approximation was performed on the most energetically favored WS2 /AlN. The G0 W0 calculations revealed that the heterostructure of WS2 /AlN at d 2 having a bandgap of 3 eV. The Bethe-Salpeter equation on top of G0 W0 calculations showed that the exciton state having the binding energy of 0.64 eV.